Analisis Rasio Untuk Menilai Kinerja Keuangan Daerah Kabupaten Batang Hari Tahun 2014-2019 - Sri Rosmawati; Febriana Kartikasari (LEMBAGA PENELITIAN DAN PENGABDIAN PADA MASYARAKAT STIE-GRAHA KARYA MUARA BULIAN, 2020)
The purpose of this study are: (1) To determine the development of Regional Original Revenue in Batang Hari Regency in 2014-2019. (2) To determine the effectiveness ratio of the Regional Original Revenue of Batang Hari Regency in 2014-2019. (3) To determine the ratio of Independence of Regional Original Revenue in Batang Hari Regency in 2014-2019, the research method used is descriptive quantitative. The type of data used is secondary data from the Batang Hari APBD which has been published during the 2014-2019 period obtained from www.djpk.kemenkeu.go.id. The results showed that the development of local revenue in Batang Hari Regency during the 2014-2019 period fluctuated. The fluctuation that is shown is not only an increase but also a decrease. The results of the calculation of the effectiveness ratio of Batang Hari Regency PAD for the 2014-2019 period show that it is effective for 2014. Meanwhile, for 2018 and 2019, the effectiveness ratio is ineffective, because it is still below 100 percent, which means that the target of Regional Original Income has not been achieved. The Independence Ratio of Batang Hari Regency for the period 2014-2019 shows that the criteria for the independence of Batang Hari Regency are very lacking.